The Use of Omega-3 Fatty Acids as an Alternative Treatment for Attention Deficit Hyperactivity Disorder in Children - Samra M. Suliman, (Journal of King Abdulaziz University: Medical Sciences, 2023)
This case report studies the effi cacy of omega-3 fatty acids as an alternative to using psychopharmacological agents for treating patients with Attention-Deficit Hyperactivity Disorder. While this study may not end the controversy concerning the eff ectiveness of omega-3, it does establish a very solid case for using omega-3 fatty acids as an augmenting agent along with a lower than recommended minimum starting stimulant dose.